Sewage sludge ash characteristics and potential for use in concrete. (15th November 2015) - Lynn, Ciarán J.; Dhir, Ravindra K.; Ghataora, Gurmel S.; West, Roger P.
Highlights: Globally published literature on SSA use in concrete analysed and evaluated. SSA use as raw feed for cement and in ground form as cement component. SSA use as fine and filler aggregates and in lightweight manufactured aggregates. Use in bulk quantities in CLSM, aerated and foamed concrete. Suggestions for developing SSA as value-added sustainable construction material. Abstract: Sewage sludge ash (SSA) use in concrete related applications is assessed through systematic review involving analysis and evaluation of the global literature found published since 1983. The material characteristics indicate potential for various applications: in small dosages as raw feed in Portland cement production, as fine and filler aggregates, or in ground form as cement component, with manageable effects on performance. Using manufactured SSA aggregate, concrete strength suitable for structural applications and lightweight properties comparable to Leca are attainable. SSA can be used in bulk, in controlled low strength materials (CLSM), aerated and foamed concretes. Reported case studies give encouraging signals.